Post-COVID-19 Pandemic Sequelae in Liver Diseases - Cristina Stasi (Life)
During the coronavirus disease 2019 (COVID-19) pandemic, several studies highlighted a worse prognosis for patients with alterations in liver function tests, especially those with pre-existing liver diseases. However, further studies are needed to define the long-term impact of the COVID-19 pandemic on liver diseases. Long COVID-19 encompasses a wide range of signs and symptoms, including exacerbations of pre-existing chronic conditions or new onset conditions developed after the COVID-19 acute phase. Therefore, the long-term effects of COVID-19 extensively include hepatic manifestations. The co-expression of angiotensin-converting receptor 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2) has been demonstrated also in enterocytes, cholangiocytes, and hepatocytes. Studies on the post-COVID-19 sequelae have shown the presence of steatosis and necroinflammation in the liver, concomitantly with an alteration of inflammation, cytolysis and cholestasis indices. Some studies also demonstrated an increased risk for hepatobiliary pathologies, including secondary biliary cholangitis and worsening of the severity of metabolic-associated fatty liver disease (MASLD). Based on these premises, this review aims to provide an overview of the pathophysiological mechanisms contributing to COVID-19-related liver and hepatobiliary damage; explore its implications for liver inflammation and fibrosis, with a particular focus on MASLD and metabolic dysfunction-associated steatohepatitis (MASH); and analyze the short- and long-term COVID-19 sequelae. A literature search was conducted using the PubMed database for relevant studies published in English.